3D Time Resolved Temperature and concentration Measurement using Background Oriented Quantitative Schlieren Technique - Iffa, Emishaw; Azia, A. Rashid; Malik, Aamir Saeed (2010)
In this paper, background-oriented schlieren technique is employed for simultaneous measurement of concentration and temperature fields of a gas flow. The gas samples used were an injected compressed Natural gas (CNG) fuel and methane flame. Since both flows had exhibited a strong axi-symmetry a single camera projection was sufficient enough for reconstruction of a volumetric field. The displacement vectors were calculated using phasebased correlation techniques. Affine motion model is used because it accounts for both translational and rotational motions of the background. Based on our synthetic data evaluation, complex wavelet-based phase correlation is insensitive to llumination variation and is a more robust deflection-vector estimation method. This estimation was more useful for the flame flow which creates a considerable intensity variation between the pair of images under correlation. Principles of geometric optics were used in order to get the index of refraction. The density information was recovered by slotting in Gladstone-Dale equation in filtered back projection. Finally, the computed three dimensional concentration and temperature parameters are shown as a function of time.